ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENGGUNAAN LAHAN PERKOTAAN PENDEKATAN SPATIAL ECONOMETRICS: STUDI KASUS PERKOTAAN DIY, 2011 - Prastowo, Prastowo (Jurnal Ekonomi & Studi Pembangunan, 2016)
This paper aims to demonstrate the effect of economic growth on the urban land use. This study used data area according to the type of land use by district building yard to measure urban land. In addition, to illustrate economic growth the use of PDB regional, the authors found that 1 percent increase in PDB regional resulted in changes of urban land uses amounted to 0.55 percent in DIY urban areas. Increasing urban land use implictions for the expansion of urban land in DIY. Result show that economic growth are particulay important urban land use in DIY urban areas.